2014
DOI: 10.1186/1476-7120-12-43
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac calcium score on 2D echo: correlations with cardiac and coronary calcium at multi-detector computed tomography

Abstract: BackgroundTo test the hypothesis that a semi-quantitative echocardiographic calcium score (eCS) significantly correlates with cardiac calcium measured by coronary computed tomography angiography (CCTA) and, secondarily, severe coronary artery calcifications and stenosis.MethodsThis is a retrospective, observational study, conducted in a tertiary centre. eCS was compared with CCTA scores of non-coronary cardiac calcium (nCACS), coronary cardiac calcium (CACS) and number of diseased coronary vessels, in 141 subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Cardiac calcium is more robustly proven as a parameter acquired outside of this stress echocardiography setting, during standard rest echocardiography, when it has an incredible long-standing “career” since the first 1999 NEJM outcome paper in which, specifically for the aortic valve,[ 17 ] the association between cardiac calcium and mortality became first widely known, and this association in general for cardiac calcium also assessed in the mitral valve or other sites remained valid both for diagnostic and prognostic purposes in primary prevention prospective studies. [ 18 19 20 21 22 23 ] Several types of scores have also been built and tested assessing the grade of sclerosis-calcification of the aortic valve, mitral valve, ascending aorta, and sometimes papillary muscles, but, in general, some structured assessment of echogenicity and thickening of at least aortic and mitral valves is enough, and the presence of zero cardiac calcium versus moderate-severe calcium does help to stratify the absence or presence of obstructive CAD or future cardiovascular events. Importantly, this variable or score adds incrementally to wall motion behavior assessed during stress echocardiography, which makes ultrasound cardiac calcium scoring another good candidate as an additional parameter in this context.…”
Section: W Hich a Re The M mentioning
confidence: 99%
“…Cardiac calcium is more robustly proven as a parameter acquired outside of this stress echocardiography setting, during standard rest echocardiography, when it has an incredible long-standing “career” since the first 1999 NEJM outcome paper in which, specifically for the aortic valve,[ 17 ] the association between cardiac calcium and mortality became first widely known, and this association in general for cardiac calcium also assessed in the mitral valve or other sites remained valid both for diagnostic and prognostic purposes in primary prevention prospective studies. [ 18 19 20 21 22 23 ] Several types of scores have also been built and tested assessing the grade of sclerosis-calcification of the aortic valve, mitral valve, ascending aorta, and sometimes papillary muscles, but, in general, some structured assessment of echogenicity and thickening of at least aortic and mitral valves is enough, and the presence of zero cardiac calcium versus moderate-severe calcium does help to stratify the absence or presence of obstructive CAD or future cardiovascular events. Importantly, this variable or score adds incrementally to wall motion behavior assessed during stress echocardiography, which makes ultrasound cardiac calcium scoring another good candidate as an additional parameter in this context.…”
Section: W Hich a Re The M mentioning
confidence: 99%
“…5 Coronary angiotomography is known to predict individual risk of coronary events, evaluating the calcium score of the coronary arteries and the semiquantitative scores of valvular calcium. 5 A study by Gaibazzi et al 6 has established a cardiac calcification index by TTE and predicted the presence of important coronary calcification, with results comparable to those of coronary angiotomography. 6 In patients with coronary artery disease (CAD), mitral annular calcification and aortic valve sclerosis on TTE are independent risk factors for cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…5 A study by Gaibazzi et al 6 has established a cardiac calcification index by TTE and predicted the presence of important coronary calcification, with results comparable to those of coronary angiotomography. 6 In patients with coronary artery disease (CAD), mitral annular calcification and aortic valve sclerosis on TTE are independent risk factors for cardiovascular events. 7 Some studies have shown that calcium deposition in the aortic leaflets and fibrous skeleton at the base of the heart is related to aging.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, conventional echocardiographic examination may offer a semi-quantitative assessment of cardiac calcifications at different sites: the mitral apparatus (annulus, leaflets and papillary muscles), aortic valve and ascending aorta 16 (Figures 1 and 2). Calcification of intracardiac structures on echocardiography corresponds to valve calcium detected by CT, and is also related to CAC (Figure 3).…”
Section: Introductionmentioning
confidence: 99%